Lithium ion adsorbent material, method for preparing the same, and use thereof
Patent Information
- Application Number
- CN202410336415.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-22
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-03-22
AI Technical Summary
Existing lithium-ion sieves have poor flowability and water wettability in industrial applications, resulting in low circulation efficiency, easy loss, high energy consumption, and the use of binders can cover active sites, affecting lithium extraction capacity and speed.
A porous polymer sponge was used as a carrier to load lithium-ion sieves, avoiding the use of binders. The lipophilic modified lithium-ion sieves were used as Pickering emulsion emulsifiers to prepare porous polymer sponges, forming a through-pore macroporous structure. The lithium-ion sieves were deposited on the inner wall, and non-covalent cross-linking points were formed by using bifunctional monomers to provide compressive strength and resilience.
This method achieves high loading capacity and high dispersion fixation of lithium ion sieves, improves lithium ion diffusion rate, enhances lithium extraction capacity and efficiency, and ensures the stability and liquid flowability of the lithium extraction process.
Smart Images

Figure CN118403619B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion resource extraction technology, and relates to a lithium-ion adsorption material, its preparation method and application. Background Technology
[0002] Liquid lithium resources, such as salt lake brines, are generally characterized by low lithium-ion concentrations, high magnesium-to-lithium ratios, complex compositions, and numerous associated elements. Coupled with a lack of mature separation and extraction technologies, liquid lithium resources cannot yet be industrially developed and utilized on a large scale. Currently, to achieve the separation and extraction of lithium ions from liquid lithium resources, researchers have successively developed methods such as calcination impregnation, solar evaporation, co-precipitation, solvent extraction, and adsorption.
[0003] Among these methods, adsorption is a relatively ideal technique for extracting lithium ions from seawater or salt lakes. Adsorption uses adsorbents selectively targeting lithium ions to adsorb them. Based on the mechanism of ion exchange, after the target lithium ions are extracted (in a lithium-depleted state), they can be reintroduced and react to form a composite material (in a lithium-rich state). Therefore, it is more suitable for the separation and enrichment of lithium ions in large-scale liquid environments, and also has the advantages of low energy consumption, environmental friendliness, and ease of operation.
[0004] The key to the adsorbent method is the use of high-performance and highly stable lithium-ion adsorbents. Lithium-ion sieves are a special type of lithium-ion adsorbent with high adsorption capacity and high selectivity. Currently, lithium-ion sieves mainly include three categories: manganese-based lithium-ion sieves (LMO), titanium-based lithium-ion sieves (LTO), and aluminum-based adsorbents (LiAl-LDHs), as well as phosphate, silicate, and antimonate materials. However, regardless of the type of lithium-ion sieve, the synthesized product is mostly in powder form. In industrial applications, it has poor flowability, poor water wettability, low circulation efficiency, is not easy to separate from aqueous environments and is easily lost, which can lead to large pressure drops and high energy consumption in column operations, thus hindering industrial applications. Existing technologies usually use granulation, film formation, foaming, and electrospinning for reshaping, but these methods all use polymers as binders or loading materials, which can cause the active sites of the lithium-ion sieve to be covered by the binder, resulting in a decrease in lithium extraction capacity and rate.
[0005] Therefore, a new technical solution needs to be developed to avoid the impact of binder use on lithium-ion sieve molding, thereby obtaining a high-performance and highly stable lithium extraction material. Summary of the Invention
[0006] In view of the problems existing in the prior art, the purpose of this invention is to provide a lithium-ion adsorbent material, its preparation method, and its applications. This invention can fix lithium-ion sieves to form lithium-ion adsorbent materials without using binders, thereby achieving better lithium extraction performance and stability.
[0007] To achieve this objective, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a lithium-ion adsorption material, comprising a porous polymer sponge and a lithium-ion sieve loaded in the porous polymer sponge.
[0009] This invention uses a porous polymer sponge as a carrier to fix a lithium-ion sieve onto the inner wall of the sponge's pores without using an adhesive. The high specific surface area of the porous polymer sponge not only allows for high-load, highly dispersed fixation of the lithium-ion sieve but also limits its position to prevent loss, resulting in better lithium extraction performance and stability of the lithium-ion adsorption material. Utilizing the compressible and resilient properties of the porous polymer sponge, liquid lithium resources can be discharged and absorbed through compression, thereby promoting liquid flow during the lithium extraction process and improving extraction efficiency.
[0010] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. The technical objectives and beneficial effects of the present invention can be better achieved and realized through the following technical solutions.
[0011] As a preferred embodiment of the present invention, the lithium-ion sieve includes a lithium-poor titanium-based lithium-ion sieve, wherein the titanium-based lithium-ion sieve comprises Li₂TiO₃ or Li₄Ti₅O₃. 12 .
[0012] Preferably, the lithium-ion sieve has an average particle size of 200-300 nm and a particle size dispersion coefficient of 0.15-0.5.
[0013] In a second aspect, the present invention provides a method for preparing the lithium-ion adsorbent material described in the first aspect, the method comprising:
[0014] Lithium-ion sieves were modified with lipophilic properties and then used as emulsifiers.
[0015] The monomer, initiator, emulsifier, water and oil phase solvent are mixed to obtain an O / W type high internal phase Pickering emulsion.
[0016] The obtained O / W type high internal phase Pickering emulsion was subjected to heating reaction and extraction in sequence to obtain lithium ion adsorption material.
[0017] This invention uses an oleophilically modified lithium-ion sieve as an emulsifier in a Pickering emulsion to prepare a porous polymer sponge using a high internal phase template method. The resulting porous polymer sponge has a typical through-pore structure, which allows the lithium-ion sieve to deposit on the inner wall of the porous polymer sponge, forming a lithium-ion adsorbent material. At the same time, the abundant gaps and large specific surface area of the lithium-ion adsorbent material are also conducive to improving the diffusion rate of lithium ions, thereby improving the lithium extraction capacity and lithium extraction efficiency.
[0018] As a preferred embodiment of the present invention, the lithium-ion sieve is in a lithium-poor state.
[0019] Preferably, the method for modifying the lithium ion sieve to be oleophilic includes: mixing the lithium ion sieve with an aqueous solution of hexadecyltrimethylammonium bromide at a concentration of (8-12) mg / mL at a solid-liquid ratio of (0.8-1.2) g / 100 mL.
[0020] As a preferred embodiment of the present invention, the preparation method further includes:
[0021] The monomer, initiator, emulsifier, and water are mixed to prepare an aqueous solution. Then, the oil phase solvent is added to the aqueous solution, and the mixture is homogenized at 18,000–22,000 rpm for 3–7 min to obtain an O / W type high internal phase Pickering emulsion.
[0022] Preferably, the monomer has a mass percentage concentration of 20% to 25% in the aqueous solution.
[0023] Preferably, the mass of the initiator is 2% to 4% of the mass of the monomer.
[0024] Preferably, the initiator comprises potassium persulfate.
[0025] Preferably, the concentration of the emulsifier in the aqueous solution is (1-1.6) g / 10 mL.
[0026] Preferably, the volume ratio of the oil phase solvent to the aqueous phase solution is 5:(1.25~1.75).
[0027] Preferably, the oil phase solvent includes at least one of cyclohexane, n-hexane, cyclopentane, pentane, n-heptane, or isooctane.
[0028] As a preferred technical solution of the present invention, the monomer includes monofunctional monomers and difunctional monomers.
[0029] Preferably, the molar ratio of the monofunctional monomer to the difunctional monomer is 1:(0.2 to 0.4).
[0030] Preferably, the monofunctional monomer includes at least one of acrylic acid, methacrylic acid, acrylamide, methacrylamide, hydroxyethyl acrylate, or hydroxyethyl methacrylate.
[0031] Preferably, the bifunctional monomer comprises a vinyl-terminated polyurethane prepolymer and methylenebisacrylamide.
[0032] Preferably, the molar ratio of the vinyl-terminated polyurethane prepolymer to the methylenebisacrylamide is (0.3-0.5):1.
[0033] This invention uses a bifunctional monomer as a crosslinking agent. The vinyl-terminated polyurethane prepolymer has an OCONH-R-NHCOO structure, where R is a hexamethylene or benzene ring. It exhibits regularity, and the OCONH-R-NHCOO structural units between different chain segments can stack through hydrogen bonds and / or π-π interactions to form non-covalent crosslinking points. These points can serve as stress dissipation points during the compression of porous polymer sponges, providing the porous polymer sponges with good compressive strength and resilience. This enables the lithium-ion adsorbent material to extract lithium through squeezing out liquid and then reabsorbing it, while ensuring long-term stability during use.
[0034] As a preferred embodiment of the present invention, the method for preparing the vinyl-terminated polyurethane prepolymer includes:
[0035] Polyol and a first difunctional isocyanate compound were stirred in a solvent at room temperature for 4–6 hours. Then, a second difunctional isocyanate compound was added and stirred for another 2–4 hours to obtain a polyurethane prepolymer. Hydroxyethyl methacrylate was then added to carry out a capping reaction to obtain a vinyl-capped polyurethane prepolymer.
[0036] Preferably, the solvent includes at least one of N,N-dimethylformamide (DMF), dichloromethane (DCM), dimethyl sulfoxide (DMSO), toluene, or chloroform, with chloroform being the most preferred.
[0037] Preferably, the molar ratio of the polyol, the first difunctional isocyanate compound, and the second difunctional isocyanate compound is 1:1:(0.08-0.12).
[0038] Preferably, the polyol comprises polyethylene glycol or polybutanediol, and the number average molecular weight of the polyol is 200 to 600.
[0039] Preferably, the first difunctional isocyanate compound and the second difunctional isocyanate compound are independently selected from at least one of hexamethylene diisocyanate (HDI), dimethyl diisocyanate or xylene diisocyanate.
[0040] Preferably, the ratio of the total molar amount of the first difunctional isocyanate compound and the second difunctional isocyanate compound to the molar amount of the hydroxyethyl methacrylate is 1:(2 to 2.4).
[0041] As a preferred embodiment of the present invention, the heating reaction temperature is 60-80°C and the time is 12-36 hours.
[0042] Preferably, the extraction method includes Soxhlet extraction.
[0043] Preferably, the extractant used in the Soxhlet extraction method includes acetone.
[0044] Thirdly, the present invention provides an application of the lithium-ion adsorbent material described in the first aspect, the application including lithium extraction from liquid lithium ore resources.
[0045] As a preferred technical solution of the present invention, the method for extracting lithium from liquid lithium ore resources includes: after the lithium ion adsorbent material absorbs liquid to reach liquid absorption equilibrium, performing lithium ion deintercalation; squeezing the lithium ion adsorbent material to drain the liquid and reabsorbing liquid to reach liquid absorption equilibrium, performing lithium ion deintercalation; and repeating the liquid drainage and liquid absorption process.
[0046] As a preferred technical solution of the present invention, after the lithium-ion adsorption material reaches liquid absorption equilibrium and before compression, the lithium-ion deintercalation time is 10 to 30 minutes.
[0047] Compared with existing technical solutions, the present invention has at least the following beneficial effects:
[0048] The lithium-ion adsorption material of this invention uses a porous polymer sponge as a carrier to fix a lithium-ion sieve, avoiding the influence of using binders. This not only achieves high loading and high dispersion fixation of the lithium-ion sieve, but also uses the porous polymer sponge to limit the position of the lithium-ion sieve to prevent its loss, resulting in better lithium-ion diffusion rate, thereby improving lithium extraction capacity and efficiency, and achieving better lithium extraction performance and stability. Utilizing the compressible and resilient properties of the porous polymer sponge, liquid lithium resources can be discharged and absorbed through compression, thereby promoting liquid flow during the lithium extraction process and further improving lithium extraction efficiency.
[0049] This invention uses a specific bifunctional monomer as a crosslinking agent to form non-covalent crosslinking points, which serve as stress dissipation points during the compression process of porous polymer sponges. This provides the porous polymer sponges with good compressive strength and resilience, thereby enabling the lithium-ion adsorbent material to extract lithium through a process of squeezing out liquid and reabsorbing liquid, while ensuring long-term stability during use. Attached Figure Description
[0050] Figure 1This is a SEM image of the lithium-ion adsorbent material obtained in Example 1.
[0051] Figure 2 It is a lithium extraction device containing the lithium-ion adsorption material described in this invention.
[0052] Figure 2 In the middle: 1-container, 2-lithium ion adsorption material, 3-piston, 4-solution to be extracted or delithiated. Detailed Implementation
[0053] The technical solution of the present invention will be further illustrated below through specific embodiments.
[0054] Those skilled in the art should understand that the embodiments described are merely to help understand the present invention and should not be regarded as specific limitations on the present invention.
[0055] [Lithium-ion adsorption materials]
[0056] In some specific embodiments, the present invention provides a lithium-ion adsorption material, comprising a porous polymer sponge and a lithium-ion sieve loaded in the porous polymer sponge.
[0057] In one embodiment, the lithium-ion sieve comprises a lithium-poor titanium-based lithium-ion sieve, wherein the titanium-based lithium-ion sieve comprises Li₂TiO₃ or Li₄Ti₅O₃. 12 .
[0058] In one embodiment, the average particle size of the lithium-ion sieve is 200-300 nm, for example, it can be 200 nm, 220 nm, 240 nm, 260 nm, 280 nm or 300 nm, and the particle size distribution index (PDI) is 0.15-0.5, for example, it can be 0.15, 0.25, 0.35, 0.45 or 0.5, but it is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0059] In this invention, the lithium-rich titanium-based lithium-ion sieve is abbreviated as LTO, and the lithium-depleted titanium-based lithium-ion sieve is abbreviated as HTO. It is understood that when preparing the lithium-ion adsorption material of this invention for lithium extraction, the lithium-ion sieve should be in a lithium-depleted state; when performing delithiation, the lithium-ion sieve should be in a lithium-rich state.
[0060] [Preparation Method of Lithium-ion Adsorption Materials]
[0061] In some specific embodiments, the present invention provides a method for preparing the lithium-ion adsorbent material described in the above embodiments, the preparation method comprising:
[0062] Lithium-ion sieves were modified with lipophilic properties and then used as emulsifiers.
[0063] The monomer, initiator, emulsifier, water and oil phase solvent are mixed to obtain an O / W type high internal phase Pickering emulsion.
[0064] The obtained O / W type high internal phase Pickering emulsion was subjected to heating reaction and extraction in sequence to obtain lithium ion adsorption material.
[0065] In the O / W type high internal phase Pickering emulsion of the present invention, the aqueous phase is the external phase and the oil phase is the internal phase.
[0066] In one embodiment, the lithium-ion sieve is prepared by a sol-gel method.
[0067] In one embodiment, prior to the oleophilic modification, the lithium-ion sieve is subjected to delithiation treatment to convert it into a lithium-poor state.
[0068] In one embodiment, the delithiation process includes an acid washing process.
[0069] In one embodiment, the method for lipophilic modification of the lithium-ion sieve includes: mixing the lithium-ion sieve with an aqueous solution of hexadecyltrimethylammonium bromide (CTAB) at a concentration of (8-12) mg / mL at a solid-liquid ratio of (0.8-1.2) g / 100 mL; the solid-liquid ratio may be 0.8 g / 100 mL, 0.9 g / 100 mL, 1 g / 100 mL, 1.1 g / 100 mL, or 1.2 g / 100 mL, etc.; the concentration may be 8 mg / mL, 9 mg / mL, 10 mg / mL, 11 mg / mL, or 12 mg / mL, etc., but is not limited to the values listed, and other unlisted values within the above range are also applicable.
[0070] In one embodiment, the preparation method further includes:
[0071] The monomer, initiator, emulsifier, and water are mixed to prepare an aqueous solution. Then, the oil phase solvent is added to the aqueous solution, and the mixture is homogenized at 18,000 to 22,000 rpm for 3 to 7 minutes to obtain an O / W type high internal phase Pickering emulsion. The above-mentioned rotation speed can be 18,000 rpm, 19,000 rpm, 20,000 rpm, 21,000 rpm, or 22,000 rpm, etc. The above-mentioned homogenization time can be 3 minutes, 4 minutes, 5 minutes, 6 minutes, or 7 minutes, etc., but is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0072] In one embodiment, the mass percentage concentration of the monomer in the aqueous solution is 20% to 25%, for example, it can be 20%, 21%, 22%, 23%, 24% or 25%, etc., but is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0073] In one embodiment, the mass of the initiator is 2% to 4% of the mass of the monomer, for example, it can be 2%, 2.5%, 3%, 3.5% or 4%, etc., but is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0074] In one embodiment, the initiator comprises potassium persulfate.
[0075] In one embodiment, the concentration of the emulsifier in the aqueous solution is (1 to 1.6) g / 10 mL, for example, it can be 1 g / 10 mL, 1.1 g / 10 mL, 1.2 g / 10 mL, 1.3 g / 10 mL, 1.4 g / 10 mL, 1.5 g / 10 mL or 1.6 g / 10 mL, etc., but is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0076] In one embodiment, the volume ratio of the oil phase solvent to the aqueous phase solution is 5:(1.25 to 1.75), such as 5:1.25, 5:1.35, 5:1.45, 5:1.55, 5:1.65 or 5:1.75, but is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0077] In one embodiment, the oil phase solvent includes at least one of cyclohexane, n-hexane, cyclopentane, pentane, n-heptane, or isooctane. Typical but non-limiting combinations include combinations of cyclohexane and n-hexane, cyclohexane and cyclopentane, cyclohexane and pentane, cyclohexane and n-heptane, cyclohexane and isooctane, n-hexane and cyclopentane, cyclopentane and pentane, or n-heptane and isooctane, etc.
[0078] In one embodiment, the monomer includes monofunctional monomers and difunctional monomers.
[0079] In one embodiment, the molar ratio of the monofunctional monomer to the difunctional monomer is 1:(0.2 to 0.4), for example, it can be 1:0.2, 1:0.25, 1:0.3, 1:0.35 or 1:0.4, but it is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0080] In one embodiment, the monofunctional monomer includes at least one of acrylic acid, methacrylic acid, acrylamide, methacrylamide, hydroxyethyl acrylate, or hydroxyethyl methacrylate. Typical but non-limiting examples of combinations include combinations of acrylic acid and acrylamide, combinations of acrylic acid and hydroxyethyl acrylate, combinations of methacrylic acid and acrylamide, combinations of methacrylic acid and hydroxyethyl acrylate, or combinations of methacrylamide and hydroxyethyl methacrylate.
[0081] In one embodiment, the bifunctional monomer comprises a vinyl-terminated polyurethane prepolymer and methylenebisacrylamide.
[0082] In one embodiment, the molar ratio of the vinyl-terminated polyurethane prepolymer to the methylenebisacrylamide is (0.3 to 0.5):1, for example, it can be 0.3:1, 0.35:1, 0.4:1, 0.45:1 or 0.5:1, but is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0083] In one embodiment, a method for preparing the vinyl-terminated polyurethane prepolymer includes:
[0084] Polyol and a first difunctional isocyanate compound are stirred in a solvent at room temperature for 4–6 hours, such as 4 hours, 4.5 hours, 5 hours, 5.5 hours, or 6 hours. Then, a second difunctional isocyanate compound is added and stirred for another 2–4 hours, such as 2 hours, 2.5 hours, 3 hours, 3.5 hours, or 4 hours, to obtain a polyurethane prepolymer. Hydroxyethyl methacrylate is then added for end-capping to obtain a vinyl-terminated polyurethane prepolymer. The stirring time is not limited to the values listed above, and other unlisted values within the above range are also applicable.
[0085] In one embodiment, the molar ratio of the polyol, the first difunctional isocyanate compound, and the second difunctional isocyanate compound is 1:1:(0.08 to 0.12), for example, it can be 1:1:0.08, 1:1:0.09, 1:1:0.1, 1:1:0.11, or 1:1:0.12, but it is not limited to the values listed above. Other unlisted values within the above range are also applicable.
[0086] In one embodiment, the polyol includes polyethylene glycol or polybutanediol, and the number average molecular weight of the polyol is 200 to 600, such as 200, 300, 400, 500 or 600, but is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0087] In one embodiment, the first difunctional isocyanate compound and the second difunctional isocyanate compound are independently selected from at least one of hexamethylene diisocyanate, phenylene diisocyanate, or xylene diisocyanate. Typical but non-limiting combinations include combinations of hexamethylene diisocyanate and phenylene diisocyanate, combinations of hexamethylene diisocyanate and xylene diisocyanate, or combinations of phenylene diisocyanate and xylene diisocyanate.
[0088] In one embodiment, the ratio of the total molar amount of the first difunctional isocyanate compound and the second difunctional isocyanate compound to the molar amount of the hydroxyethyl methacrylate is 1:(2 to 2.4), for example, it can be 1:2, 1:2.1, 1:2.2, 1:2.3 or 1:2.4, but it is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0089] In one embodiment, the heating reaction temperature is 60–80°C, such as 60°C, 65°C, 70°C, 75°C, or 80°C, and the time is 12–36 hours, such as 12 hours, 16 hours, 20 hours, 24 hours, 28 hours, 32 hours, or 36 hours, but is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0090] In one embodiment, the extraction method includes Soxhlet extraction.
[0091] In one embodiment, the extractant used in the Soxhlet extraction method includes acetone.
[0092] In one embodiment, the Soxhlet extraction is performed for 1 to 3 days, such as 1 day, 2 days or 3 days, but not limited to the listed values. Other unlisted values within the above range are also applicable.
[0093] Applications of lithium-ion adsorption materials
[0094] In some specific embodiments, the present invention provides an application of the lithium-ion adsorbent material described in the above embodiments, the application including lithium extraction from liquid lithium ore resources.
[0095] In one embodiment, the method for extracting lithium from liquid lithium ore resources includes: after the lithium ion adsorbent material absorbs liquid to reach liquid absorption equilibrium, performing lithium ion deintercalation; squeezing the lithium ion adsorbent material to drain the liquid and reabsorbing liquid to reach liquid absorption equilibrium, performing lithium ion deintercalation again; and repeating the draining and absorption processes.
[0096] In one embodiment, after the lithium-ion adsorbent material reaches liquid absorption equilibrium and before compression, the lithium-ion deintercalation time is 10 to 30 minutes, for example, 10 minutes, 15 minutes, 20 minutes, 25 minutes or 30 minutes, but not limited to the listed values. Other unlisted values within the above range are also applicable.
[0097] [Lithium Extraction Equipment]
[0098] In some specific embodiments, the present invention provides a lithium extraction device for implementing the method for extracting lithium from liquid lithium ore resources as described in the above embodiments.
[0099] In one implementation, such as Figure 2 As shown, the lithium extraction device includes a container 1 with an open top and an opening at the bottom. The container 1 is filled with the lithium ion adsorption material 2 described in the above embodiment. A piston 3 is provided at the open top of the container 1 and extends into the container 1. The piston 3 is used to squeeze and drain the lithium ion adsorption material 2 and to reabsorb the liquid.
[0100] In some specific embodiments, the present invention provides a method for operating the lithium extraction device described in the above embodiments. The method includes: placing the lithium extraction device in a solution 4 to be lithium extracted or delithiated, allowing the lithium ion adsorbent material 2 to reach liquid absorption equilibrium, performing a lithium ion insertion or extraction process for 10 to 30 minutes, opening the piston 3 to squeeze the lithium ion adsorbent material 2 to discharge the internal liquid, then releasing the pressure to allow the lithium ion adsorbent material 2 to reabsorb liquid and reach liquid absorption equilibrium, performing a lithium ion insertion or extraction process for 10 to 30 minutes, and repeating the liquid discharge and liquid absorption process until the lithium extraction or delithiation target is achieved.
[0101] Example 1
[0102] This embodiment provides a lithium-ion adsorbent material, the preparation method of which includes:
[0103] (1) Preparation of lithium-rich lithium-ion sieves by sol-gel method
[0104] Lithium acetate was dissolved in an ethanol-water solution (v / v = 3 / 1) to obtain solution A with a concentration of 0.15 g / mL; tetrabutyl titanate was dissolved in a mixed solution of acetic acid and ethanol (v / v = 1 / 3) to obtain solution B with a concentration of 0.35 g / mL; solution A was slowly added dropwise to solution B while stirring at 500 rpm, controlling the molar ratio Li / Ti = 2:1. After the addition was complete, stirring was continued for 1 h, and then the solution was placed in a vacuum drying oven and dried at 80 °C to form a gel; the gel was then calcined in a muffle furnace at 600 °C for 4 h at a heating rate of 3 °C / min, and then cooled to room temperature at a cooling rate of 3 °C / min to obtain nano-Li₂TiO₃ with an average particle size of 240 nm and a particle size distribution coefficient of 0.22;
[0105] (2) Preparation of lithium-depleted lithium-ion sieves by acid elution and delithiation
[0106] The nano-Li₂TiO₃ obtained in step (1) was placed in a 0.25 mol / L hydrochloric acid solution and acid-washed for 24 hours at room temperature with stirring, in order to remove the Li₂TiO₃. + Replace with H + After washing and filtration, the material is dried in a vacuum drying oven for 12 hours to obtain nano-HTO lithium ion sieves.
[0107] (3) Lipophilic modification
[0108] The nano-HTO lithium ion sieve obtained in step (2) was dispersed in an aqueous solution of 10 mg / mL CTAB at a solid-liquid ratio of 1 g: 100 mL, sonicated at room temperature for 2 h, then centrifuged, sonicated and washed in the aqueous solution, repeated three times, and dried at 80 °C to obtain modified nano-HTO.
[0109] (4) Preparation of aqueous solution
[0110] Methacrylic acid, acrylamide, vinyl-terminated polyurethane prepolymer, methylenebisacrylamide, and potassium persulfate were dissolved in water to form a monomer aqueous solution. Then, the modified nano-HTO obtained in step (3) was dispersed in the monomer aqueous solution to obtain an aqueous phase solution. The molar ratio of methacrylic acid, acrylamide, vinyl-terminated polyurethane prepolymer, and methylenebisacrylamide was controlled to be 0.7:0.3:0.11:0.29, and the mass percentage concentration of the monomer in the aqueous phase solution was controlled to be 23%. The mass of potassium persulfate was controlled to be 3% of the total mass of the monomer. The concentration of modified nano-HTO in the aqueous phase solution was controlled to be 1.3 g / 10 mL.
[0111] The preparation method of the vinyl-terminated polyurethane prepolymer is as follows: Polybutanediol (Mn = 400 g / mol), the first difunctional isocyanate compound MDI, and the catalyst dibutyltin dilaurate are placed in a reactor containing chloroform solvent, stirred evenly, and reacted at 80°C for 1 hour. Then, the second difunctional isocyanate compound MDI is added and the reaction is continued for 3 hours with the stirring speed maintained at 140 rpm. Finally, hydroxyethyl methacrylate is added and the reaction is continued for 0.8 hours. The molar ratio of polybutanediol, the first difunctional isocyanate compound, the second difunctional isocyanate compound, and hydroxyethyl methacrylate is controlled to be 1:1:0.1:2.42, and the amount of dibutyltin dilaurate added is controlled to be 2% of the total mass of the difunctional isocyanate compound. When the NCO content (titrated by di-n-butylamine method) is less than 1%, the reaction is stopped by cooling, thus obtaining the vinyl-terminated polyurethane prepolymer.
[0112] (5) Preparation of O / W type high internal phase Pickering emulsion
[0113] The oil phase solvent cyclohexane was added to the aqueous phase solution obtained in step (4), and the volume ratio of the oil phase solvent to the aqueous phase solution was controlled to be 5:1.5. The mixture was homogenized at 20,000 rpm for 5 min to obtain an O / W type high internal phase Pickering emulsion.
[0114] (6) Heating reaction and extraction
[0115] The O / W type high internal phase Pickering emulsion obtained in step (5) was transferred to a hydrothermal reactor, sealed, and placed in an oven to be heated to 70°C for 24 hours to obtain a block polymer. The block polymer was then extracted with acetone as the extractant using Soxhlet extraction for 2 days and dried in an 80°C blast oven to obtain a lithium ion adsorbent material.
[0116] Example 2
[0117] This embodiment provides a lithium-ion adsorbent material. In step (4), the concentration of modified nano-HTO in the aqueous solution is adjusted from 1.3 g / 10 mL to 1 g / 10 mL. Otherwise, the other conditions are exactly the same as in Example 1.
[0118] Example 3
[0119] This embodiment provides a lithium-ion adsorbent material. In step (4), the concentration of modified nano-HTO in the aqueous solution is adjusted from 1.3 g / 10 mL to 1.6 g / 10 mL. Otherwise, the other conditions are exactly the same as in Example 1.
[0120] Example 4
[0121] This embodiment provides a lithium-ion adsorbent material. In step (4), the concentration of modified nano-HTO in the aqueous solution is adjusted from 1.3 g / 10 mL to 0.7 g / 10 mL. Otherwise, the other conditions are exactly the same as in Example 1.
[0122] Example 5
[0123] This embodiment provides a lithium-ion adsorbent material. In step (4), the concentration of modified nano-HTO in the aqueous solution is adjusted from 1.3 g / 10 mL to 1.9 g / 10 mL. Otherwise, the other conditions are exactly the same as in Example 1.
[0124] Example 6
[0125] This embodiment provides a lithium-ion adsorbent material, the preparation method of which includes:
[0126] (1) Preparation of lithium-rich lithium-ion sieves by sol-gel method
[0127] Lithium acetate was dissolved in an ethanol-water solution (v / v = 3 / 1) to obtain solution A with a concentration of 0.15 g / mL; tetrabutyl titanate was dissolved in a mixed solution of acetic acid and ethanol (v / v = 1 / 3) to obtain solution B with a concentration of 0.35 g / mL; solution A was slowly added dropwise to solution B at a stirring speed of 1000 rpm, controlling the molar ratio Li / Ti = 2:1. After the addition was complete, stirring was continued for 1 h, and then the solution was placed in a vacuum drying oven and dried at 80 °C to form a gel; the gel was then calcined in a muffle furnace at 600 °C with a heating rate of 2 °C / min for 4 h, and then cooled to room temperature at a cooling rate of 3 °C / min to obtain nano-Li₂TiO₃ with an average particle size of 200 nm and a particle size distribution coefficient of 0.15;
[0128] (2) Preparation of lithium-depleted lithium-ion sieves by acid elution and delithiation
[0129] The nano-Li₂TiO₃ obtained in step (1) was placed in a 0.25 mol / L hydrochloric acid solution and acid-washed for 24 hours at room temperature with stirring, in order to remove the Li₂TiO₃. + Replace with H + After washing and filtration, the material is dried in a vacuum drying oven for 12 hours to obtain nano-HTO lithium ion sieves.
[0130] (3) Lipophilic modification
[0131] The nano-HTO lithium ion sieve obtained in step (2) was dispersed in an aqueous solution of 10 mg / mL CTAB at a solid-liquid ratio of 1 g: 100 mL, sonicated at room temperature for 2 h, then centrifuged, sonicated and washed in the aqueous solution, repeated three times, and dried at 80 °C to obtain modified nano-HTO.
[0132] (4) Preparation of aqueous solution
[0133] Methacrylic acid, acrylamide, vinyl-terminated polyurethane prepolymer, methylenebisacrylamide, and potassium persulfate were dissolved in water to form a monomer aqueous solution. Then, the modified nano-HTO obtained in step (3) was dispersed in the monomer aqueous solution to obtain an aqueous solution. The molar ratio of methacrylic acid, acrylamide, vinyl-terminated polyurethane prepolymer, and methylenebisacrylamide was controlled to be 0.7:0.3:0.07:0.23, and the mass percentage concentration of the monomer in the aqueous solution was controlled to be 23%. The mass of potassium persulfate was controlled to be 3% of the total mass of the monomer. The concentration of modified nano-HTO in the aqueous solution was controlled to be 1.3 g / 10 mL.
[0134] The preparation method of the vinyl-terminated polyurethane prepolymer is as follows: Polybutanediol (Mn = 400 g / mol), the first difunctional isocyanate compound MDI, and the catalyst dibutyltin dilaurate are placed in a reactor containing chloroform solvent, stirred evenly, and reacted at 80°C for 1 hour. Then, the second difunctional isocyanate compound MDI is added and the reaction is continued for 3 hours with the stirring speed maintained at 140 rpm. Finally, hydroxyethyl methacrylate is added and the reaction is continued for 0.8 hours. The molar ratio of polybutanediol, the first difunctional isocyanate compound, the second difunctional isocyanate compound, and hydroxyethyl methacrylate is controlled to be 1:1:0.1:2.42, and the amount of dibutyltin dilaurate added is controlled to be 2% of the total mass of the difunctional isocyanate compound. When the NCO content (titrated by di-n-butylamine method) is less than 1%, the reaction is stopped by cooling, thus obtaining the vinyl-terminated polyurethane prepolymer.
[0135] (5) Preparation of O / W type high internal phase Pickering emulsion
[0136] The oil phase solvent cyclohexane was added to the aqueous phase solution obtained in step (4), and the volume ratio of the oil phase solvent to the aqueous phase solution was controlled to be 5:1.25. The mixture was homogenized at 20000 rpm for 5 min to obtain an O / W type high internal phase Pickering emulsion.
[0137] (6) Heating reaction and extraction
[0138] The O / W type high internal phase Pickering emulsion obtained in step (5) was transferred to a hydrothermal reactor, sealed, and placed in an oven to be heated to 70°C for 24 hours to obtain a block polymer. The block polymer was then extracted with acetone as the extractant using Soxhlet extraction for 2 days and dried in an 80°C blast oven to obtain a lithium ion adsorbent material.
[0139] Example 7
[0140] This embodiment provides a lithium-ion adsorbent material, the preparation method of which includes:
[0141] (1) Preparation of lithium-rich lithium-ion sieves by sol-gel method
[0142] Lithium acetate was dissolved in an ethanol-water solution (v / v = 3 / 1) to obtain solution A with a concentration of 0.18 g / mL; tetrabutyl titanate was dissolved in a mixed solution of acetic acid and ethanol (v / v = 1 / 3) to obtain solution B with a concentration of 0.41 g / mL; solution A was slowly added dropwise to solution B while stirring at 500 rpm, controlling the molar ratio Li / Ti = 2:1. After the addition was complete, stirring was continued for 1 h, and then the solution was placed in a vacuum drying oven and dried at 80 °C to form a gel; the gel was then calcined in a muffle furnace at 600 °C for 4 h with a heating rate of 5 °C / min, and then cooled to room temperature at a cooling rate of 3 °C / min to obtain nano-Li₂TiO₃ with an average particle size of 290 nm and a particle size distribution coefficient of 0.45;
[0143] (2) Preparation of lithium-depleted lithium-ion sieves by acid elution and delithiation
[0144] The nano-Li₂TiO₃ obtained in step (1) was placed in a 0.25 mol / L hydrochloric acid solution and acid-washed for 24 hours at room temperature with stirring, in order to remove the Li₂TiO₃. + Replace with H + After washing and filtration, the material is dried in a vacuum drying oven for 12 hours to obtain nano-HTO lithium ion sieves.
[0145] (3) Lipophilic modification
[0146] The nano-HTO lithium ion sieve obtained in step (2) was dispersed in an aqueous solution of 10 mg / mL CTAB at a solid-liquid ratio of 1 g: 100 mL, sonicated at room temperature for 2 h, then centrifuged, sonicated and washed in the aqueous solution, repeated three times, and dried at 80 °C to obtain modified nano-HTO.
[0147] (4) Preparation of aqueous solution
[0148] Methacrylic acid, acrylamide, vinyl-terminated polyurethane prepolymer, methylenebisacrylamide, and potassium persulfate were dissolved in water to form a monomer aqueous solution. Then, the modified nano-HTO obtained in step (3) was dispersed in the monomer aqueous solution to obtain an aqueous phase solution. The molar ratio of methacrylic acid, acrylamide, vinyl-terminated polyurethane prepolymer, and methylenebisacrylamide was controlled to be 0.7:0.3:0.16:0.34, and the mass percentage concentration of the monomer in the aqueous phase solution was controlled to be 23%. The mass of potassium persulfate was controlled to be 3% of the total mass of the monomer. The concentration of the modified nano-HTO in the aqueous phase solution was controlled to be 1.3 g / 10 mL.
[0149] The preparation method of the vinyl-terminated polyurethane prepolymer is as follows: Polybutanediol (Mn = 400 g / mol), the first difunctional isocyanate compound MDI, and the catalyst dibutyltin dilaurate are placed in a reactor containing chloroform solvent, stirred evenly, and reacted at 80°C for 1 hour. Then, the second difunctional isocyanate compound MDI is added and the reaction is continued for 3 hours with stirring speed maintained at 140 rpm. Finally, hydroxyethyl methacrylate is added and the reaction is continued for 0.8 hours. The molar ratio of polybutanediol, the first difunctional isocyanate compound, the second difunctional isocyanate compound, and hydroxyethyl methacrylate is controlled to be 1:1:0.1:2.42, and the amount of dibutyltin dilaurate added is controlled to be 2% of the total mass of the difunctional isocyanate compound. When the NCO content (titrated by di-n-butylamine method) is less than 1%, the reaction is stopped by cooling, thus obtaining the vinyl-terminated polyurethane prepolymer.
[0150] (5) Preparation of O / W type high internal phase Pickering emulsion
[0151] The oil phase solvent cyclohexane was added to the aqueous phase solution obtained in step (4), and the volume ratio of the oil phase solvent to the aqueous phase solution was controlled to be 5:1.75. The mixture was homogenized at 20,000 rpm for 5 min to obtain an O / W type high internal phase Pickering emulsion.
[0152] (6) Heating reaction and extraction
[0153] The O / W type high internal phase Pickering emulsion obtained in step (5) was transferred to a hydrothermal reactor, sealed, and placed in an oven to be heated to 70°C for 24 hours to obtain a block polymer. The block polymer was then extracted with acetone as the extractant using Soxhlet extraction for 2 days and dried in an 80°C blast oven to obtain a lithium ion adsorbent material.
[0154] Comparative Example 1
[0155] This comparative example uses the nano-HTO lithium ion sieve obtained in step (2) of Example 1 for subsequent testing.
[0156] [Performance Testing]
[0157] I. The microstructure of the material was observed using a JEOL JSM-6490LV scanning electron microscope.
[0158] Figure 1 This is a SEM image of the lithium-ion adsorbent material obtained in Example 1. As can be seen from the image, the porous polymer sponge possesses a rich hierarchical pore structure. Figure 1 The top left corner shows an enlarged view of the inner wall of the porous polymer sponge pores, which shows that the lithium-ion sieve particles were successfully loaded and fixed on the inner wall of the porous polymer sponge pores.
[0159] II. The specific surface area of the material was analyzed using an ASAP2020M specific surface area and microporous adsorption analyzer. N2 adsorption / desorption was performed under liquid nitrogen, and the specific surface area of the sample was calculated using the BET formula.
[0160] III. Adsorption capacity test:
[0161] The lithium-ion adsorbent materials obtained in Examples 1-7 were processed into 5×5×5cm cubic sponges, and then used as described in the above embodiments. Figure 2 The lithium extraction apparatus shown is used to extract lithium at 25°C. The apparatus is immersed in a lithium-containing solution (Li) in a reaction tank. + The concentration is 0.05 mol / L. The total amount of lithium-containing solution is controlled according to a solid-liquid ratio (S / L) of 1 g: 1000 mL between the lithium ion sieve in the cubic sponge and the lithium-containing solution. Following the working method of the lithium extraction device provided in the above embodiment, after the cubic sponge is completely immersed in the lithium-containing solution and reaches liquid absorption equilibrium, a lithium ion intercalation process is performed for 20 minutes. Then, the piston is activated to drain the adsorbent material and allow it to reabsorb liquid. This process constitutes one cycle and is repeated 10 times.
[0162] Because Comparative Example 1 cannot use, Figure 2 The lithium extraction device shown was tested. Therefore, using existing technology, an equal amount of nano-HTO lithium-ion sieve as in Example 1 was mixed with a binder, granulated, and then subjected to a static adsorption test, as follows: The lithium-ion sieve granules were immersed in a lithium-containing solution (Li... + The solution was prepared at a concentration of 0.05 mol / L (with a solid-liquid ratio of 1 g: 1000 mL) and shaken at 100 rpm in a constant temperature shaker at 25 °C for 4 h.
[0163] ICP-OES was used to determine the Li in the solution. + The adsorption capacity Q is calculated using the following formula: e (mg / g):
[0164]
[0165] In the formula, C0 (mg / L) represents Li + The initial concentration of C; e (mg / L) is the concentration of lithium ions when adsorption equilibrium is reached; V(L) is the volume of the solution; m(g) is the mass of the lithium ion adsorption material obtained in the examples or the nano HTO lithium ion sieve of Comparative Example 1.
[0166] IV. The compressibility of the lithium-ion adsorbent material obtained in the example was tested using an INSTRON 3344 electronic universal testing machine. The sample size was a cylinder with a diameter of 20 mm and a height of 10 mm. The compression rate was 5 mm / min. The stress value when the material was compressed to 60% was tested and recorded. After 100 compression cycles, the stress value of the 100th compression cycle was recorded.
[0167] The test results are recorded in Table 1.
[0168] Table 1
[0169]
[0170] The loading amount in Table 1 is calculated based on the mass of the lithium-ion adsorption material product obtained by the preparation method of lithium-ion adsorption material and the amount of lithium-depleted lithium-ion sieve.
[0171] From the above, we can see that:
[0172] The lithium-ion adsorbent material obtained in Example 1 has excellent lithium extraction capacity and capacity retention rate. Its compressive strength is sufficient to allow it to extract lithium through repeated compression and rebound, thereby improving the lithium extraction efficiency.
[0173] Examples 2-5 adjusted the amount of lithium-poor modified lithium-ion sieve as emulsifier. When the loading was insufficient, the lithium extraction capacity of the obtained lithium-ion adsorption material decreased significantly. When the loading was too high, the capacity retention rate and compressive strength were affected. Therefore, in practical applications, the loading should be adjusted reasonably so that the comprehensive performance of lithium extraction capacity and capacity retention rate can reach the most suitable working state.
[0174] Comparative Example 1 uses the nano-HTO lithium-ion sieve obtained in step (2) as the lithium-ion adsorbent material. Compared with Example 1, it has a lower adsorption capacity. This is because, for the same adsorption time, Example 1 uses... Figure 2 The apparatus shown performs accelerated adsorption, while Comparative Example 1 uses static adsorption, which results in a lower adsorption efficiency than Example 1.
[0175] This invention uses a porous polymer sponge as a carrier to fix a lithium-ion sieve, avoiding the influence of binders. This not only achieves high-load, highly dispersed fixation of the lithium-ion sieve, but also uses the porous polymer sponge to limit the position of the sieve, preventing its loss. This results in better lithium-ion diffusion rate in the lithium-ion adsorbent material, thereby improving lithium extraction capacity and efficiency, and achieving better lithium extraction performance and stability. Utilizing the compressible and resilient properties of the porous polymer sponge, liquid lithium resources can be discharged and absorbed through compression, promoting liquid flow during the lithium extraction process and further improving extraction efficiency. This invention uses a specific bifunctional monomer as a crosslinking agent to form non-covalent crosslinking points, which serve as stress dissipation points during the compression process of the porous polymer sponge. This provides the porous polymer sponge with good compressive strength and resilience, enabling the resulting lithium-ion adsorbent material to extract lithium through compression drainage and reabsorption, while ensuring long-term stability.
[0176] This invention illustrates the detailed process equipment and process flow through the above embodiments. However, this invention is not limited to the detailed process equipment and process flow described above, meaning that this invention does not necessarily depend on the detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvements to this invention, equivalent substitutions of raw materials for the product of this invention, addition of auxiliary components, and selection of specific methods, all fall within the protection scope and disclosure scope of this invention.
[0177] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.
[0178] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.
[0179] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.
Claims
1. A lithium-ion adsorbent material, characterized in that, It includes a porous polymer sponge and a lithium-ion sieve loaded in the porous polymer sponge; The preparation method of the lithium-ion adsorbent material includes: Lithium-ion sieves were modified with lipophilic properties and then used as emulsifiers. The monomer, initiator, emulsifier, water and oil phase solvent are mixed to obtain an O / W type high internal phase Pickering emulsion. The obtained O / W type high internal phase Pickering emulsion was subjected to heating reaction and extraction in sequence to obtain lithium ion adsorption material; The monomers include monofunctional monomers and difunctional monomers; The monofunctional monomer includes at least one of acrylic acid, methacrylic acid, acrylamide, methacrylamide, hydroxyethyl acrylate, or hydroxyethyl methacrylate. The bifunctional monomers include vinyl-terminated polyurethane prepolymers and methylenebisacrylamide.
2. The lithium-ion adsorbent material according to claim 1, characterized in that, The lithium-ion sieve includes a lithium-poor titanium-based lithium-ion sieve, which comprises Li₂TiO₃ or Li₄Ti₅O₃. 12 .
3. The lithium-ion adsorbent material according to claim 1, characterized in that, The lithium-ion sieve has an average particle size of 200~300nm and a particle size dispersion coefficient of 0.15~0.
5.
4. A method for preparing the lithium-ion adsorbent material according to any one of claims 1-3, characterized in that, The preparation method includes: Lithium-ion sieves were modified with lipophilic properties and then used as emulsifiers. The monomer, initiator, emulsifier, water and oil phase solvent are mixed to obtain an O / W type high internal phase Pickering emulsion. The obtained O / W type high internal phase Pickering emulsion was subjected to heating reaction and extraction in sequence to obtain lithium ion adsorption material; The monomers include monofunctional monomers and difunctional monomers; The monofunctional monomer includes at least one of acrylic acid, methacrylic acid, acrylamide, methacrylamide, hydroxyethyl acrylate, or hydroxyethyl methacrylate. The bifunctional monomers include vinyl-terminated polyurethane prepolymers and methylenebisacrylamide.
5. The method for preparing the lithium-ion adsorbent material according to claim 4, characterized in that, The lithium-ion sieve is in a lithium-poor state.
6. The method for preparing the lithium-ion adsorbent material according to claim 4, characterized in that, The method for modifying lithium ion sieves to be oleophilic includes: mixing lithium ion sieves with an aqueous solution of hexadecyltrimethylammonium bromide at a concentration of (8~12) mg / mL at a solid-liquid ratio of (0.8~1.2) g / 100 mL.
7. The method for preparing the lithium-ion adsorbent material according to claim 4, characterized in that, The preparation method further includes: The monomer, initiator, emulsifier, and water are mixed to prepare an aqueous solution. Then, the oil phase solvent is added to the aqueous solution, and the mixture is homogenized at 18,000 to 22,000 rpm for 3 to 7 minutes to obtain an O / W type high internal phase Pickering emulsion.
8. The method for preparing the lithium-ion adsorbent material according to claim 7, characterized in that, The monomer has a mass percentage concentration of 20% to 25% in the aqueous solution.
9. The method for preparing the lithium-ion adsorbent material according to claim 7, characterized in that, The mass of the initiator is 2% to 4% of the mass of the monomer.
10. The method for preparing the lithium-ion adsorbent material according to claim 7, characterized in that, The initiator includes potassium persulfate.
11. The method for preparing the lithium-ion adsorbent material according to claim 7, characterized in that, The concentration of the emulsifier in the aqueous solution is (1~1.6) g / 10 mL.
12. The method for preparing the lithium-ion adsorbent material according to claim 7, characterized in that, The volume ratio of the oil phase solvent to the aqueous phase solution is 5:(1.25~1.75).
13. The method for preparing the lithium-ion adsorbent material according to claim 7, characterized in that, The oil phase solvent includes at least one of cyclohexane, n-hexane, cyclopentane, pentane, n-heptane, or isooctane.
14. The method for preparing the lithium-ion adsorbent material according to claim 4, characterized in that, The molar ratio of the monofunctional monomer to the difunctional monomer is 1:(0.2~0.4).
15. The method for preparing the lithium-ion adsorbent material according to claim 4, characterized in that, The molar ratio of the vinyl-terminated polyurethane prepolymer to the methylene bisacrylamide is (0.3~0.5):
1.
16. The method for preparing the lithium-ion adsorbent material according to claim 4, characterized in that, The method for preparing the vinyl-terminated polyurethane prepolymer includes: Polyol and a first difunctional isocyanate compound were stirred in a solvent at room temperature for 4-6 hours, and then a second difunctional isocyanate compound was added and stirred for 2-4 hours to obtain a polyurethane prepolymer. Hydroxyethyl methacrylate was then added for end-capping to obtain a vinyl-terminated polyurethane prepolymer.
17. The method for preparing the lithium-ion adsorbent material according to claim 16, characterized in that, The molar ratio of the polyol, the first difunctional isocyanate compound, and the second difunctional isocyanate compound is 1:1:(0.08~0.12).
18. The method for preparing the lithium-ion adsorbent material according to claim 16, characterized in that, The polyol includes polyethylene glycol or polybutanediol, and the number average molecular weight of the polyol is 200-600.
19. The method for preparing the lithium-ion adsorbent material according to claim 16, characterized in that, The first difunctional isocyanate compound and the second difunctional isocyanate compound are independently selected from at least one of hexamethylene diisocyanate, phenylenediamine diisocyanate or xylene diisocyanate.
20. The method for preparing the lithium-ion adsorbent material according to claim 16, characterized in that, The ratio of the total molar amount of the first and second difunctional isocyanate compounds to the molar amount of the hydroxyethyl methacrylate is 1:(2~2.4).
21. The method for preparing the lithium-ion adsorbent material according to claim 4, characterized in that, The heating reaction is carried out at a temperature of 60-80°C for a duration of 12-36 hours.
22. The method for preparing the lithium-ion adsorbent material according to claim 4, characterized in that, The extraction method includes Soxhlet extraction.
23. The method for preparing the lithium-ion adsorbent material according to claim 22, characterized in that, The Soxhlet extraction method uses acetone as the extraction solvent.
24. The use of a lithium-ion adsorbent material according to any one of claims 1-3, characterized in that, The applications include extracting lithium from liquid lithium ore resources.
25. The use of the lithium-ion adsorbent material according to claim 24, characterized in that, The method for extracting lithium from liquid lithium ore resources includes: after the lithium ion adsorbent material absorbs liquid to reach liquid absorption equilibrium, performing lithium ion deintercalation; squeezing the lithium ion adsorbent material to drain the liquid and reabsorbing liquid to reach liquid absorption equilibrium, performing lithium ion deintercalation again; and repeating the draining and absorption process.
26. The use of the lithium-ion adsorbent material according to claim 25, characterized in that, After the lithium-ion adsorbent material reaches liquid absorption equilibrium and before compression, the lithium-ion deintercalation time is 10-30 minutes.
Citation Information
Patent Citations
Lithium adsorbent forming process using sponge as vector
CN102160992A
